2018
DOI: 10.1371/journal.pcbi.1006303
|View full text |Cite
|
Sign up to set email alerts
|

Paxillin phosphorylation at serine 273 and its effects on Rac, Rho and adhesion dynamics

Abstract: Focal adhesions are protein complexes that anchor cells to the extracellular matrix. During migration, the growth and disassembly of these structures are spatiotemporally regulated, with new adhesions forming at the leading edge of the cell and mature adhesions disassembling at the rear. Signalling proteins and structural cytoskeletal components tightly regulate adhesion dynamics. Paxillin, an adaptor protein within adhesions, is one of these proteins. Its phosphorylation at serine 273 (S273) is crucial for ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(75 citation statements)
references
References 70 publications
7
68
0
Order By: Relevance
“…In this study, we identified two paxillin-WT adhesion subpopulations experimentally: one was small dynamic adhesions and one was larger stable adhesions 48 . This bimodality was abolished experimentally with expression of paxillin-S273D or S273A mutants, which had predominantly small, dynamic or large, stable adhesions, respectively 48 . The model also identified a bistable switch consistent with the two populations of adhesions, dynamic or stable.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In this study, we identified two paxillin-WT adhesion subpopulations experimentally: one was small dynamic adhesions and one was larger stable adhesions 48 . This bimodality was abolished experimentally with expression of paxillin-S273D or S273A mutants, which had predominantly small, dynamic or large, stable adhesions, respectively 48 . The model also identified a bistable switch consistent with the two populations of adhesions, dynamic or stable.…”
Section: Discussionmentioning
confidence: 91%
“…This data will be valuable for the development of new computational models of cell migration and adhesion. In fact, we have already used the data to develop a new model that has helped us to further understand the role of paxillin S273 phosphorylation and its effects on the small GTPases Rac1 and RhoA in regulating adhesion dynamics 48 . In this study, we identified two paxillin-WT adhesion subpopulations experimentally: one was small dynamic adhesions and one was larger stable adhesions 48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated paxillin phosphorylation is common in cancer tissues and is associated with tumorigenesis, EMT, and metastasis 15,16,50 . Paxillin interacts with numerous molecules, controlling the Rho family of GTPases, that are crucial regulators of adhesion dynamics 16,51 . Rac1 GTPase is required for cell migration and its hyperactivation results in cancer invasiveness and progression 52 .…”
Section: Discussionmentioning
confidence: 99%
“…As in the previous model, we used quantitative mass spectrometry data to determine the prevailing protein isoforms of the RhoA-Rac1 network in MDA-MB-231 cells, as well as the protein abundances. The parameters of activation and deactivation of RhoA, Rac1 and PAK were estimated based on the literature data ( Lyda et al, 2019 ; Tang et al, 2018 ). The parameters of activation and deactivation of DIA and ROCK were estimated based on typical association and dissociation constants of protein-protein interactions ( Kholodenko et al, 1999 ).…”
Section: Methodsmentioning
confidence: 99%